IMPLEMENTATION AND AWARENESS OF E-LEARNING IN MALAYSIA: A BIBLIOMETRICS RESEARCH - Wan Azani Mustafa; Ernie Adnan; Noor Hidayah Che Lah; Abdul Ghafur Hanafi; Wan Zuki Azman Wan Muhamad; Fathullah Asni, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The implementation and awareness with regard to e-learning in Malaysia have gained significant attention, particularly in response to the growing digital transformation in education. While e-learning presents opportunities for improved accessibility and flexible learning environments, challenges such as digital readiness, technological infrastructure, and engagement persist. The goal of this study is to assess the research landscape towards e-learning implementation and awareness in Malaysia through a bibliometric approach. We analyzed 723 relevant publications from the Scopus database using Scopus Analyzer and VOSviewer software. These tools facilitated the extraction of prevalent keywords, co-occurrence patterns, and collaborative research trends, which are summarized in the form of occurrence rates and total link strength among keywords. The findings indicate that research interest in e-learning has significantly increased, particularly post-2020, caused by the influence of the COVID-19 pandemic. Note that the most frequently occurring keywords include “e-learning,” “online learning,” “implementation” and “awareness” highlighting the dominant themes in this field. Additionally, co-authorship analysis reveals Malaysia’s strong research collaboration with countries like the United Kingdom, Indonesia, and Saudi Arabia, further solidifying its role as a leader in digital education research. Despite the progress, challenges such as limited access in rural areas, digital literacy gaps, and technological resistance remain key obstacles to successful e-learning adoption. This study provides valuable insights into research trends, enabling policymakers, educators as well as researchers to establish more efficient strategies in order to integrate e-learning into Malaysia’s education system. Future studies should explore the integration of emerging technologies, digital equity, and post-pandemic e-learning sustainability in ensuring long-term success in digital education.